Gas‐Phase Generation and Decomposition of a Sulfinylnitrene into the Iminyl Radical OSN. Issue 4 (17th December 2015) - Wu, Zhuang; Li, Dingqing; Li, Hongmin; Zhu, Bifeng; Sun, Hailong; Francisco, Joseph S.; Zeng, Xiaoqing
Abstract: The dipolar oxathiazyne‐like sulfinylnitrene RS(O)N, a highly reactive α‐oxo nitrene, has been rarely investigated. Upon flash vacuum pyrolysis of sulfinyl azide CF3 S(O)N3 at 350 °C, an elusive sulfinylnitrene CF3 S(O)N was generated in the gas phase in its singlet ground state and was characterized by matrix‐isolation IR spectroscopy. Further fragmentation of CF3 S(O)N at 600 °C produced CF3 and a novel iminyl radical OSN, an SO2 analogue, which were unambiguously identified by IR spectroscopy. Consistent with the experimental observations, DFT calculations clearly support a stepwise decomposition mechanism of CF3 S(O)N3 . Abstract : The triatomic molecule OSN was generated from the stepwise decomposition of gaseous CF3 S(O)N3 via the novel sulfinyl nitrene CF3 S(O)N. Matrix IR spectroscopy and DFT calculations were employed to identify and characterize the matrix‐isolated decomposition products and to elucidate the reaction mechanism.